Development of An Arabic E-Magazine on Jumla Ismiyah Learning Topics - Ud Ulana Setiawan; Atiqoh Atiqoh; Hari Karyono (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to develop E-Magazine-based learning media in Arabic language learning in high school with a focus on jumla ismiyah material. The research method used is Research and Development (R&D) following the Dick and Carey ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Based on the results of the study showed that at the validation stage of an E-Magazine developed for Arabic language learning on jumla ismiyah material at SMA Muhammadiyah 4 Surabaya, which consisted of 3 validations, namely material experts who had a validity value of 91.11%, media experts produced a very high score, which was 94.11%, and design experts had a validity value of 88.11%, all of which were included in the very valid category. Meanwhile, the validation of the E-Magazine learning media response test on students showed that small and extensive field trials had validity rates of 89.81% and 89.94%, respectively, which consistently showed that E-Magazine was very feasible to be used as a learning medium and received a positive response from students. The conclusion is that the development of an E-Magazine for Arabic language learning is very feasible to be implemented with an excellent percentage of learning success.